What the Best Law Teacher s Do - Michael Hunter Schwartz, Gerald F. Hess, and Sophie M. Sparrow (Harvard University Press, 2013)
Who was your best teacher, law or otherwise? What made that teacher so effective? For the past four years, we have posed these questions at conferences, law schools, and to groups of Chilean, Georgian, Ira ni an, and Turkish law teachers. In response, law teachers have described their best teachersâ€™ attitudes, expectations, teaching methods, mental habits, beliefs about students and learning, personal qualities, teaching emphases, and anything else that made their teachers so noteworthy. The results have been strikingly similar. Across cultures and schools, the best teachers distinguish themselves by their thoughtfulness, caring about their students, high expectations, commitment to student learning, and ability to engage their students.Those same qualities distinguish the twenty- six law teachers we have written about in this book. Starting in spring 2008, we sought to study extraordinary law teachers, teachers who have a signifi cant, positive, and long- term effect on their students. Our goal was to create the fi rst systematic, rigorous study of excellent law teaching. We have written and read a number of scholarly efforts at synthesizing the teaching and learning research from other fi elds; we wanted to contribute something new that would be credible to our colleagues. We also were cognizant that other works have identifi ed many ways legal education and law teachers need to change; we wanted to offer something different. This book is the product of that four- and- a-half- year study. In the pro cess, we have reviewed hundreds of nominations and visited the law schools where the subjects of this book were teaching. We observed each subject teach, interviewed their students, and scrutinized thousands of pages of interview transcripts, student evaluations, testimonial letters, and teaching materials. We recognize that the term â€œbestâ€ is hard to defi ne, as we explain below. However, we believe that we have identifi ed twenty- six great US law teachers. We chose the title for this book, What the Best Law Teachers Do, for several reasons. First, it echoes the title of its pre deces sor book, Ken Bainâ€™s What the Best College Teachers Do. Second, we believe that our results also refl ect not only what excellent law teachers do, but also what excellent teachers in other fi elds do.